Children with autism in a sport and physical activity context: a collaborative autoethnography by two parents outlining their experiences. Issue 9 (21st November 2020) - McMahon, Jenny; Wiltshire, Gilly-Elle; McGannon, Kerry R.; Rayner, Christopher
ABSTRACT: Sport and physical activity contexts are entrenched with ableist perspectives which view disability as abnormal or negative. Consequently, those who deviate from cultural norms may experience inequity, exclusion, stigmatisation, non-accidental violence and maltreatment. Despite the commitment to ensuring sport and physical activity is safe and inclusive through policies and programmes, more knowledge is needed about the welfare-related experiences of persons with a disability in sport and physical activity to better protect them. This research used collaborative autoethnography and Goffman's theory of stigma to explore two mothers' experiences in a sport and physical activity context, including what they saw, what they felt and what they perceived their children with a disability experienced. This research shows both mothers experienced stigma (e.g. enacted, courtesy, affiliate) due to their immersion and the actions of others in these contexts. Further, both mothers also perceived that their children with a disability experienced the same types of stigma in these contexts as well as the negative consequences related to this stigma (e.g. bullying, social isolation, exclusion, judgement, labelling, anxiety). These acts of stigmatisation positioned both them and their children as outsiders within the stories. This collaborative autoethnography highlights the lack of provisions for disabled children and their families in sport and physical activity contexts, and the persistence of ableist views.